BIODIVERSITAS Basidiomycetes DIKECAMATAN KELILA, KABUPATEN JAYAWIJAYA, PROVINSI PAPUA DAN MANFAATNYA SEBAGAI BAHAN MAKANAN DAN OBAT TRADISIONAL - Imamuddin, Hartati; Suliasih, Suliasih (Research Center for Biology-Indonesian Institute of Sciences, 2003)
Biodiversity of Basidiomycetes was studied in Kelila, Jayawijaya, Papua.The aim of this observation was to identify species diversity of Basidiomycetes and their utilities. Sixty one species were found in the location. The 19 species were edible mushroom while 7 species have been used as traditional medicines and some species have a common odours (smell) and 1 species (Clavatia sp.) contains clavatin which could be used as arm tumour agent.